Characterization of ligand-induced thermal stability of the human organic cation transporter 2 (OCT2) - Max Maane; Fangrui Xiu; Fangrui Xiu; Peter Bellstedt; Gerd A. Kullak-Ublick; Michele Visentin (Frontiers Media S.A., 2023)
Introduction: The human organic cation transporter 2 (OCT2) is involved in the transport of endogenous quaternary amines and positively charged drugs across the basolateral membrane of proximal tubular cells. In the absence of a structure, the progress in unraveling the molecular basis of OCT2 substrate specificity is hampered by the unique complexity of OCT2 binding pocket, which seemingly contains multiple allosteric binding sites for different substrates. Here, we used the thermal shift assay (TSA) to better understand the thermodynamics governing OCT2 binding to different ligands.Methods: Molecular modelling and in silico docking of different ligands revealed two distinct binding sites at OCT2 outer part of the cleft. The predicted interactions were assessed by cis-inhibition assay using [3H]1-methyl-4-phenylpyridinium ([3H]MPP+) as a model substrate, or by measuring the uptake of radiolabeled ligands in intact cells. Crude membranes from HEK293 cells harboring human OCT2 (OCT2-HEK293) were solubilized in n-Dodecyl-β-D-Maltopyranoside (DDM), incubated with the ligand, heated over a temperature gradient, and then pelleted to remove heat-induced aggregates. The OCT2 in the supernatant was detected by western blot.Results: Among the compounds tested, cis-inhibition and TSA assays showed partly overlapping results. Gentamicin and methotrexate (MTX) did not inhibit [3H]MPP+ uptake but significantly increased the thermal stabilization of OCT2. Conversely, amiloride completely inhibited [3H]MPP+ uptake but did not affect OCT2 thermal stabilization. [3H]MTX intracellular level was significantly higher in OCT2-HEK293 cells than in wild type cells. The magnitude of the thermal shift (ΔTm) did not provide information on the binding. Ligands with similar affinity showed markedly different ΔTm, indicating different enthalpic and entropic contributions for similar binding affinities. The ΔTm positively correlated with ligand molecular weight/chemical complexity, which typically has high entropic costs, suggesting that large ΔTm reflect a larger displacement of bound water molecules.Discussion: In conclusion, TSA might represent a viable approach to expand our knowledge on OCT2 binding descriptors.